MGT910: Organization Theory - UiTM, Faculty of Business Management (2023)
Organization theory is one of the most interesting and relevant sub disciplines within the administrative sciences. Organization theory is the discipline that studies the structure of organizations and the overall organization’s ability to adapt and achieve its goals. This subject takes the perspective of using organization as the unit of analysis and takes the macro perspective of using theories to scientifically study organizations formally. This module enables participants to explore all the organizational theories as a whole and the evolution of these theories from the era of pre industrial revolution to the current contemporary theories of today. Because this is a seminar module individual research activities and written project paper will be emphasized and will be the main focus of evaluation. The candidates will be expected to study an actual organization’s situational problem in any industry. This module then, provides the opportunity to collect data that will be utilized for applications of related models recommended for solving the problem selected.